Ankyrins and Spectrins in Cardiovascular Biology and Disease - El Refaey, Mona M.; Mohler, Peter J. (Frontiers in Physiology, 2017)
Ankyrins are adaptor proteins critical for the expression and targeting of cardiac membrane proteins, signaling molecules, and cytoskeletal elements. Findings in humans and animal models have highlighted the in vivo roles for ankyrins in normal physiology and in cardiovascular disease, most notably in cardiac arrhythmia. For example, human ANK2 loss-of-function variants are associated with a complex array of electrical and structural phenotypes now termed “ankyrin-B syndrome,” whereas alterations in the ankyrin-G pathway for Nav channel targeting are associated with human Brugada syndrome. Further, both ankyrin-G and -B are now linked with acquired forms of cardiovascular disease including myocardial infarction and atrial fibrillation. Spectrins are ankyrin-associated proteins and recent studies support the critical role of ankyrin-spectrin interactions in normal cardiac physiology as well as regulation of key ion channel and signaling complexes. This review will highlight the roles of ankyrins and spectrins in cardiovascular physiology as well as illustrate the link between the dysfunction in ankyrin- and spectrin-based pathways and disease.